Coffee value chains on the move: Evidence from smallholder coffee farmers in Ethiopia - Minten, Bart; Dereje, Mekdim; Engida, Ermias; Kuma, Tadesse (Ethiopian Development Research Institute, 2015)
In this paper, we look at the coffee sector in Ethiopia and analyze changes and their drivers upstream in the value chain. In this study we focus on three main research questions. First, we study changes in coffee production practices over the last decade and then analyze how these production practices affect coffee productivity. Second, we document changes in harvest, post-harvest, marketing, and processing activities, and analyze their links with improved quality, prices, and incomes of producers. Third, we look at drivers of and constraints to change and transformation at the level of the coffee producer. For the analysis, we rely on a unique recently collected and representative large-scale survey of coffee producers and processors. To our knowledge, no other study comprising such breadth in the upstream sector has been done recently in Ethiopia, or elsewhere.1